TARI REMO DI SANGGAR TARI RAFF DANCE COMPANY SURABAYA - Subianto Karoso (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Maintaining the quality of artworks so that they continue to be of interest, one of which is to provide a platform or a place to create a work of art that can be continuously developed by establishing a studio, especially a dance studio. A dance studio is a means of carrying out energized activities. At present there are many established dance studios in the Surabaya area, one of which is the Surabaya Raff Dance Company. In the Raff Dance Company Surabaya dance studio, Remo Dance is also taught. Remo dance is a traditional dance that has become an icon of the city of Surabaya, so that its sustainability is maintained. Training activities for the Raff Dance Company Surabaya dance studio are held at the Cak Durasim Cultural Park every Wednesday and at the City Of Tomorrow Mall Sidoarjo every Saturday and Sunday.